Mean Streets: Violence against the Homeless and the Makings of a Hate Crime - Joern, Raegan (2009)
In 1999 the National Coalition for the Homeless began to document incidents of hate crime and violence against homeless people in an annual report. The statistics and stories in these reports demonstrate a disturbing rise in violent attacks and murders of homeless people across the country. This note argues that these attacks, whereby the perpetrator targets the victim because he or she is homeless, meet the legal definition for a bias motivated or hate crime. Bias motivated crimes against the homeless are bred in a social context that devalues homeless people's lives and pinpoints them as appropriate targets for violence. This note advocates for amending state hate crime law to include homeless status as a protected characteristic. Amending legislation is an appropriate and necessary means of increasing legal protection for homeless people, raising social consciousness, and addressing the harms caused by bias motivated crime